Mapping early environment using communication deviance: A longitudinal study of maternal sensitivity toward 6-month-old children. (October 2019) - de Sousa, Paulo; Sellwood, William; Fien, Kirsten; Sharp, Helen; Pickles, Andrew; Hill, Jonathan; Abbott, Kate; Fisher, Louise; Bentall, Richard P.
Abstract: Communication deviance (CD) reflects features of the content or manner of a person's speech that may confuse the listener and inhibit the establishment of a shared focus of attention. The construct was developed in the context of the study of familial risks for psychosis based on hypotheses regarding its effects during childhood. It is not known whether parental CD is associated with nonverbal parental behaviors that may be important in early development. This study explored the association between CD in a cohort of mothers ( n = 287) at 32 weeks gestation and maternal sensitivity with infants at 29 weeks in a standard play procedure. Maternal CD predicted lower overall maternal sensitivity ( B = –.385; p < .001), and the effect was somewhat greater for sensitivity to infant distress ( B = –.514; p < .001) than for sensitivity to nondistress ( B = –.311; p < .01). After controlling for maternal age, IQ and depression, and for socioeconomic deprivation, the associations with overall sensitivity and sensitivity to distress remained significant. The findings provide new pointers to intergenerational transmission of vulnerability involving processes implicated in both verbal and nonverbal parental behaviors.